Post-finasteride syndrome, - Ana Francisca Junqueira Ribeiro Pereira; Thaissa Oliveira de Almeida Coelho (Sociedade Brasileira de Dermatologia, 2020)
Abstract Finasteride is a 5α-reductase enzyme inhibitor that has been approved for the treatment of male androgenic alopecia since 1997. Over time, it has been considered a safe and well-tolerated drug with rare and reversible side effects. Recently there have been reports of adverse drug-related reactions that persisted for at least three months after discontinuation of this drug, and the term post-finasteride syndrome arose. It includes persistent sexual, neuropsychiatric, and physical symptoms. Studies to date cannot refute or confirm this syndrome as a nosological entity. If it actually exists, it seems to occur in susceptible people, even if exposed to small doses and for short periods, and symptoms may persist for long periods. Based on currently available data, the use of 5α-reductase inhibitors in patients with a history of depression, sexual dysfunction, or infertility should be carefully and individually assessed.